REPRODUKSI STEREOTIPE DAN RESISTENSI ORANG KATOBENGKE DALAM STRUKTUR MASYARAKAT BUTON - Tasrifin Tahara (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2010)
This paper aims to study the stereotypes by the kaomu-walaka group towards the Katobengke people as the less advantaged papara group. In the age of the Wolio Sultanate, the kaomu and the walaka as the dominant classes considered the Katobengke as the low social strata, or the dominated group, also called stereotyped people. However, the Katobengke has been trying to fight this definition. The forms of resistance against the kaomu-walaka group that have been done by the Katobengke include: resistance against the knowledge system of the Wolio people, resistance against their field of education, resistance by using state/military symbols, and conducting political negotiations to improve the statuses/positions of the Katobengke people in Butons social structure.Key words: Social Stratification, Stereotype, Resistence